Physico-chemical and microbiological changes during fermentation and storage of nipa sap (Nypa fruticans wurmb) - Radi, Nur Aimi (2013)
The purpose of this study is to evaluate the changes in the physico-chemical and microbiological profiles of nipa sap during natural fermentation. Natural fermentation of nipa sap involves the breakdown of carbohydrate materials under anaerobic condition with the activity of microorganisms and enzymes present. The process of fermentation is responsible for various changes of properties of nipa sap. The development of ethanol in the sap has always been the main concern related to the halal requirement and standard quality of the sap. Therefore, it is important to determine the basic properties of the sap that can be a reference to the producer. The sap from nipa palm (Nypa fruticans) was collected from local collectors. Samples were fermented at 300C for 63 days. Physical, chemical, and microbiological analyses were carried out at seven-day intervals, starting from day 0 (fresh tapping) until day 63. Physical (colour and transmittance value) and chemical analyses (ash, moisture, crude protein content, pH, total titratable acidity, total soluble solid, ethanol, sugar and organic acid contents) were carried out. The ethanol content was analysed using Headspace Gas Chromatography Mass Spectrometer (GC-MS), while the sugar and organic acid contents were analysed using High Performance Liquid Chromatography (HPLC) with Refractive Index and UV detectors, respectively. Results showed that the physical and chemical properties of fresh nipa sap were significantly different (P<0.05) compared to the fermented sap. The pH value decreased from the initial pH of 7.25 in fresh nipa sap to 3.16 in the fermented sap. The decrease in pH value correlated with the increase in organic acids content, which consisted mainly of lactic, acetic, and succinic acids. Total acidity was recorded to be 1.18% (v/v) in fresh nipa sap, and 4.59% (v/v) in the 63 day fermented sap. Succinic acid became the main contributor to the acidic condition in fermented nipa sap, with 1.83% v/v during the 63 days of fermentation, followed by lactic acid (1.67% v/v), acetic acid (0.98% v/v), tartaric acid (0.10% v/v), and pyruvic acid (<0.01% v/v). The initial concentration of ethanol in fresh nipa sap was 0.11% (v/v). Drastic increase in the ethanol content for the sample was recorded during the first seven days of fermentation (6.66% v/v), before beginning to drop slightly from day 21 (6.43% v/v) of fermentation until day 63 (5.72% v/v). The changes in other volatile compounds were also observed during fermentation, including higher alcohols, acetoin, diacetyl, and esters. Total sugar in fresh nipa sap was 16.73% (w/v), with sucrose as the main sugar present (13.33% w/v), followed by fructose (1.40% w/v), glucose (1.27% w/v), and maltose (0.73% w/v). The sugar concentration declined over the fermentation process, giving a different sugar composition in each interval day. Fructose (0.80% w/v) became the main sugar produced on the 63rd day of fermentation, followed by sucrose (0.60% w/v), glucose (0.34% w/v), and maltose (0.33% w/v). Identification of microbial species was done using the Analytical Profiling Identification system, API. The five species of yeast were identified, namely Saccharomyces cerevisiae, Cryptococcus humicola, Candida guilliermondii, Kloeckera spp., and Stephanoascus ciferii. Five species of lactic acid bacteria identified were Lactobacillus plantarum, Pediococcus spp., Streptococcus thermophilus, and Lactobacillus brevis. Acetic acid bacteria were isolated at the later stage of fermentation and identified as Acetobacter and Gluconobacter. It is concluded that the microbial species were responsible for giving the different characteristics of nipa sap during the fermentation process. It also appeared that activities brought about by microorganisms in the early stages helped the activities in the successive stages. Three stages of fermentation were revealed, including alcoholic, lactic, and acetic acid fermentation. Each stage showed specific properties and importance in order to ensure the complete cycle of the fermentation process. Further studies with a large number of samples and from various sources should be carried out in order to increase the precision of the study.